Cohesin's role in pluripotency and reprogramming. Issue 3 (1st February 2016) - Gupta, Preksha; Lavagnolli, Thais; Mira-Bontenbal, Hegias; Fisher, Amanda G.; Merkenschlager, Matthias
ABSTRACT: Cohesin is required for ES cell self-renewal and iPS-mediated reprogramming of somatic cells. This may indicate a special role for cohesin in the regulation of pluripotency genes, perhaps by mediating long-range chromosomal interactions between gene regulatory elements. However, cohesin is also essential for genome integrity, and its depletion from cycling cells induces DNA damage responses. Hence, the failure of cohesin-depleted cells to establish or maintain pluripotency gene expression could be explained by a loss of long-range interactions or by DNA damage responses that undermine pluripotency gene expression. In recent work we began to disentangle these possibilities by analyzing reprogramming in the absence of cell division. These experiments showed that cohesin was not specifically required for reprogramming, and that the expression of most pluripotency genes was maintained when ES cells were acutely depleted of cohesin. Here we take this analysis to its logical conclusion by demonstrating that deliberately inflicted DNA damage - and the DNA damage that results from proliferation in the absence of cohesin - can directly interfere with pluripotency and reprogramming. The role of cohesin in pluripotency and reprogramming may therefore be best explained by essential cohesin functions in the cell cycle.